2018
DOI: 10.20944/preprints201811.0025.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of SLM Process Parameters on the Quality of Al Alloy Parts; Part I: Powder Characterization, Density, Surface Roughness, and Dimensional Accuracy

Abstract: Additive manufacturing (AM) of high strength Al alloys promises to enhance the performance of critical components related to various aerospace and automotive applications. The key advantage of AM is its ability to generate lightweight, robust, and complex shapes. However, the characteristics of the as-built parts may represent an obstacle to satisfy the part quality requirements. The current study investigates the influence of selective laser melting (SLM) process parameters on the quality of parts fabricated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…ASTM F3049-14 was used to examine the fresh powder of AlSi10Mg and Al6061 after sieving using a 75 µm mesh. The full powder characterization of the same powders used in this study was reported by Maamoun et al [15,16]. Particle size distribution test showed a particle size ranges from 12 to 120 µm for Al6061 and from 12 to 110 µm for AlSi10Mg.…”
Section: Methodssupporting
confidence: 56%
“…ASTM F3049-14 was used to examine the fresh powder of AlSi10Mg and Al6061 after sieving using a 75 µm mesh. The full powder characterization of the same powders used in this study was reported by Maamoun et al [15,16]. Particle size distribution test showed a particle size ranges from 12 to 120 µm for Al6061 and from 12 to 110 µm for AlSi10Mg.…”
Section: Methodssupporting
confidence: 56%
“…The current study represents a comprehensive work that investigates the effect of SLM process parameters on the relative density, surface roughness, and dimensional accuracy of as-built AlSi10Mg and Al6061 parts [38]. A full characterization of both materials’ powders was presented.…”
Section: Discussionmentioning
confidence: 99%
“…Zena J Wally et al (2018) utilised the SLM procedure to create a variety of titanium micro-lattice structures using Ti-6Al-V [20]. Ahmed H et al (2018) conducted a complete experimental investigation for evaluating the outcome of SLM process parameters on the quality of the manufactured Al alloys [21]. Jan Plat et al (2020) explained that the so-called volumetric energy density (VED) can be calculated by using hatch distance and scan speed and by plugging in the laser powder, as well as by using layer thickness; such calculations would allow the SLM process to be regulated [10].…”
Section: Introductionmentioning
confidence: 99%